Mediasi Sengketa Waris di Pengadilan Agama Purworejo: Studi Putusan Nomor: 1081/Pdt.G/2019/PA.Pwr - Hari Widiyanto (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2020)
This paper discusses the process of resolving inheritance disputes through the mediation process in the Purworejo religious court, in this paper the author aims to reveal the effectiveness of dispute resolution through the mediation process, this research uses an empirical juridical method and analysis of the results of the religious court judge's decision through a copy of the peace certificate number: 1081 /Pdt.G/2019/PA.Pwr. The mediation step is an obligation for the judge to offer to the parties to the dispute, because mediation is expected to be an alternative non-legal litigation in order to reduce the pile of cases in religious courts and minimize the costs incurred by the disputing parties. Mediation conducted by the purworejo religious court judges and advocates for legal counsel from the LBH Sakti office on inheritance disputes between the defendant and the plaintiff resulted in a peaceful decision by issuing a peace deed on Wednesday 5 February 2020 in an open session.